Gambaran Determinan Remaja Gay - Siti Musyarofah; Rodhiyatun Chasanah (Universitas Ngudi Waluyo, 2019)
Various independent domestic and foreign survey institutions mentioned that inIndonesia there are 3% of LGBT people out of the total population. The rise ofLGBT phenomena in Indonesia is closely related to the trends of liberal countriesthat provide recognition and a place for LGBT communities in society. LGBT isconsidered a part of the modern life style of society which regards the view ofheterosexuality as conservative and does not apply to everyone. This study is todetermined the determinants of what makes adolescents into gay groups.Descriptive survey type research design. The sampling technique of snowballsampling, and the research respondents were 2 people. Retrieving data by indepth interview. The results showed that the determinants of gay adolescents were psychological factors, environmental factors, and economic factors. Suggestions from this research are that adolescents are expected to use their time for activities and positive things for their development, parents must give attention and affection and equip religious knowledge, and moral education to children, the government is expected to expand employment opportunities for the community